Baudelaires «Les Phares» und Nietzsches Gedicht «Das Feuerzeichen» aus dem Zyklus «Dithyramben des Dionysos»: [Baudelaire’s «The Beacons» and Nietzsche’s Poem «The Fire Signal» from the Cycle «Dithyrambs of Dionysus»] (Studia theodisca, 2017)
This essay reflects on the aesthetic and rhetorical strategies used by Nietzsche and Baudelaire in two poems, which at first glance scarcely show any resemblance. The poems are Baudelaire’s Les Phares and Nietzsche’s Feuerzeichen from the late Dithyramben. In both cases the central image of the Lighthouse and the Symbol of Light refer to the difficult relationship of the “Great Man” to the crowd; but they are also linked to the idea that “Great Men” follow their destiny of loneliness and are like stars, whose light will not be seen by others until after their death.